Effects of Coal Bottom Ash as Cementitious Material on Compressive Strength and Chloride Permeability of Concrete - Wan Ibrahim, Mohd Haziman; Ali Mangi , Sajjad; Juki, Mohd Irwan (International Journal of Sustainable Construction Engineering and Technology, 2020)
Coal Bottom Ash (CBA) is the waste material produced by coal-based power plants, particularly in Malaysia around 1.7 million tons of CBA was produced annually, which is major environmental concern. Therefore, the use of CBA as a partial replacement of cement in concrete is a possible solution for that pollution; this approach also creates a new corridor in the field of concrete production. However, this study aims to evaluate the effects of CBA as cementitious material on the concrete properties. This study incorporated 10% CBA as a cement replacement by weight method in concrete. However, concrete samples were prepared with and without CBA and immersed in water for 7, 28, 56 and 90 days. Next, the performances of concrete with and without CBA were evaluated in terms of workability, compressive strength, and rapid chloride permeability test. It was found that due to presence of CBA in concrete, workability reduces; no substantial growth in compressive strength at the early ages but substantial rise in strength was noticed after 56 days. Almost 4.7% higher strength was recorded than the control specimens at 90 days. Besides that, concrete containing CBA has lower chloride penetration as compared to the control specimen, which shows its better durability performance. It can be concluded that CBA has an enormous potential to be utilized as a cementitious material in durable concrete production.